Pengaruh Fasilitas Kerja, Motivasi Kerja dan Gaya Kepemimpinan Terhadap Kinerja Pegawai Kantor Pengadilan Agama Tanjung Karang - Praptiwi, Silvia; Rezky Amalya, Wulan (Journal of Accounting and Finance Management, 2024)
This research aims to analyze the influence of work facilities, work motivation and leadership style partially and simultaneously on employee performance as well as analyzing the variables that have the most dominant influence on employee performance at the Tanjung Karang Religious Court. The research method is survey type. Data collection techniques by collecting data through questionnaires and documentation. Researchers distributed questionnaires within the Tanjung Karang Religious Court with a total of 50 respondents. The type of data used is primary data. Hypothesis testing in this research includes reliability testing, validity testing, multiple regression analysis testing, t test (partial), and F test (simultaneous) with the help of SPSS version 26. Research results from the t test calculation (partial) can be concluded that the Facilities variable Work (X1) has no positive effect, Work Motivation (X2) has a positive effect, and Leadership Style (X3) has no positive effect. Meanwhile, the F Test (Simultaneous) Partially, Work Facilities, Work Motivation and Leadership Style together have a positive influence on the performance of Tanjung Karang Religious Court employees.